High-intensity focused ultrasound (HIFU) therapy for pain palliation in advanced stage pancreatic carcinoma: A Meta-Analysis with recent studies - Yadav, Ajay Kumar; Gnawali, Suman; Mandal , Sandip Kumar; Shrestha, Gyan Bahadur; Adhikari, Ganga Dutta; Shah, Bhanu Pratap; Yuan, Gengbiao (Nepalese Journal of Cancer, 2022)
Background: Day by day, High-intensity focused ultrasound (HIFU) therapy is becoming more familiar in medical field because it is non-invasive technique with fewer side effects and provides promising therapeutic results. Several HIFU therapy applications have approved by many approval authorities of deferent countries since last decade. It is a novel, emerging, therapeutic modality that uses ultrasound waves, propagated through tissue media, as carriers of energy. HIFU has great potential for tumor ablation and the main mechanisms of HIFU ablation involve mechanical and thermal effects. Pancreatic adenocarcinoma is currently the fourth-leading cause of cancer-related death. Up to 60–90% of patients with advanced disease suffer cancer-related pain, severely impacting their quality of life. Current management involves primarily pharmacotherapy with opioid narcotics and celiac plexus neurolysis; unfortunately, both approaches offer transient relief and cause undesired side-effects. High intensity focused ultrasound (HIFU) is a non-invasive thermal ablation technique that has been used to treat pancreatic cancer. This meta-analysis aims to evaluate the role of HIFU in pain palliation of advanced unresectable pancreatic adenocarcinoma.Methods: Paper selection was performed electronically in PubMed up to the end of March 2021, for pain palliation treatment of advanced staged pancreatic cancer with HIFU. Relevant papers were identified through the PubMed search engine using these keywords: HIFU, pancreas, pancreatic cancer, pain and palliation. Additional studies were also done included after manual search of the selected bibliographies. Palliation results reported in studies were analyzed using a logit-transformed random-effects model using the inverse variance method, with the DerSimonian-Laird estimator for t2, and Cochran’s Q test for heterogeneity among studies. The I2 was also calculated to assess the percentage of the total variability in the different effect size estimates that can be attributed to heterogeneity among the true effects and rank correlation test of funnel plot asymmetry was done to assess possible publication bias.Results: In this meta-analysis, we includes only recent 10 year studies i.e. total number of 16 studies with 687total patients with pancreatic cancer. The total patients enrolled ranges from 7 patients in the smallest series, up to 120 in the largest study. The calculated τ2was 0.187, and I2was 41%, the Q test p-value was 0. 026, is indicating significant heterogeneity among studies. The random effects estimate of the proportion of patients with pain reduction was 0.89.08.Conclusions: We concluded that HIFU performs to be an effective tool for pain palliation in advanced staged pancreatic cancer. Prospective randomized and standardized studies are necessary to confirm the effectiveness of HIFU in relieving pain, and to evaluate for any potential impact on tumor control and patient survival.